Implementasi Kurikulum Pendidikan Agama Islam di SMK Terpadu Ad-Dimyati Kota Bandung - iwan hermawan; Shalahudin Ismail; Yayat Hidayatulloh (Magister PAI Universitas Singaperbangsa Karawang, 2020)
The objectives of this study are: 1) To find out the implementation of Islamic education curriculum management in Ad-Dimyati Integrated Vocational High School (SMK) Jl. Wahid Hasyim No. 429-433 Bandung City, 2) To find out the supporting and inhibiting factors of the implementation of management of Islamic education curriculum in Ad-Dimyati Vocational High School Integrated Vocational High School. Wahid Hasyim No. 429-433 Bandung City.Data collection techniques in this study used observation, and interview techniques. While the data analysis uses descriptive analytic method, which describes the data collected in the form of words, images, and not numbers.Based on the results of research on the implementation of Islamic education curriculum in Ad-Dimyati Vocational High School (SMK) Integrated Jl. Wahid Hasyim No. 429-433 City of Bandung, the following conclusions are obtained: 1) The principal as the leader and administrator must carry out their duties regarding planning, directing activities and supervising them and as an administrator guiding teaching and learning activities. 2) Wakasek Kurukulum as the administrative manager of the teacher who is responsible for recording the completeness of the program as well as recording the implementation of the teacher's tasks and as the manager of the evaluation arranging the learning evaluation implementation tool, must always coordinate with the teacher, so that the curriculum program can be achieved by the subject teacher